2001
DOI: 10.1038/35082110
|View full text |Cite
|
Sign up to set email alerts
|

ATR/ATM-mediated phosphorylation of human Rad17 is required for genotoxic stress responses

Abstract: Genotoxic stress triggers the activation of checkpoints that delay cell-cycle progression to allow for DNA repair. Studies in fission yeast implicate members of the Rad family of checkpoint proteins, which includes Rad17, Rad1, Rad9 and Hus1, as key early-response elements during the activation of both the DNA damage and replication checkpoints. Here we demonstrate a direct regulatory linkage between the human Rad17 homologue (hRad17) and the checkpoint kinases, ATM and ATR. Treatment of human cells with genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
225
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(234 citation statements)
references
References 16 publications
6
225
1
2
Order By: Relevance
“…It is generally believed that ATR is important for sensing UV and other types of bulky damage, whereas ATM is the damage sensor for IR-and radiomimetic drug-induced DNA damage. ATR, however, serves as a backup for ATM (Abraham, 2001). Furthermore, ATR appears to be the primary sensor of replicative blockade resulting from DNA lesions other than DSBs or by mechanisms other than direct DNA damage such as those occurring in response to DNA synthesis inhibitors.…”
Section: Signal Transduction Pathways Regulating Dsb Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally believed that ATR is important for sensing UV and other types of bulky damage, whereas ATM is the damage sensor for IR-and radiomimetic drug-induced DNA damage. ATR, however, serves as a backup for ATM (Abraham, 2001). Furthermore, ATR appears to be the primary sensor of replicative blockade resulting from DNA lesions other than DSBs or by mechanisms other than direct DNA damage such as those occurring in response to DNA synthesis inhibitors.…”
Section: Signal Transduction Pathways Regulating Dsb Repairmentioning
confidence: 99%
“…In addition to these factors known to be directly involved in HRR, there are a number of molecules required for triggering DNA damage stress responses that act as 'sensors' for damage that are also important in cell cycle regulation and perhaps in the repair process itself. These sensors include ATM, ATR and DNA-PKcs (for recent reviews, see Abraham, 2001;Durocher and Jackson, 2001).…”
Section: Mechanism Of Homologous Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated PIKKs phosphorylate various downstream targets involved in controlling cell cycle checkpoints, DNA repair and apoptotic pathways. These include p53, Chk1, Chk2, Brca-1, Rad9, Rad17, H2AX and others (Canman et al, 1998;Cortez et al, 1999;Bao et al, 2001;Chen et al, 2001;Bartek and Lukas, 2003;Stiff et al, 2004). Of particular importance to checkpoint activation is p53 phosphorylation on serine 15.…”
Section: Introductionmentioning
confidence: 99%
“…For example, phosphorylation of p53, Mdm2, and Chk2 participate in the G 1 checkpoint; [11][12][13] Nbs1, Brca1, SMC1, and FancD2 participate in the transient IR-induced S-phase arrest; [14][15][16][17] and Brca1 and hRad17 have been implicated in the G2/M checkpoint. 18,19 Previous research has shown that it is possible to correct A-T deficiencies by DNA transfection in cell culture, 20,21 and that overexpression of the normal ATM protein does not cause cellular abnormalities. 22 The large size of the ATM cDNA (B9 kb) required to correct the hereditary deficiency in A-T limits use of many vectors for gene delivery.…”
Section: Introductionmentioning
confidence: 99%